RANCANG BANGUN SISTEM INFORMASI RAWAT JALAN PUSKESMAS WEEKOMBAK BERBASIS WEB - Tamo Ina, Maria; Umbu Janga, Adelbertus; Wulla Rato, Karolus (JOURNAL OF ELECTRICAL AND SYSTEM CONTROL ENGINEERING, 2024)
Information systems are created to make it easier to process and store data so that it will produce precise and accurate information. The Puskesmas Outpatient Information System is a structure that provides information to assist the decision-making process in implementing Puskesmas management in achieving its activity targets. Puskesmas as a health service requires computers as a tool for processing and presenting information. Puskesmas, which provides health services to the community on a daily basis, is a health agency sector that is growing rapidly as the population increases. A website is a system for accessing information on the internet. A website is a system for accessing information on the internet. Weekombak Community Health Center is an agency that operates in the health sector, namely providing patient care and treatment. In carrying out data processing services at the Weekombak Community Health Center, manual recording is still used, that is, all data is recorded in a book or archive. So services at Community Health Centers become ineffective and inefficient because bookkeeping media slows down the patient service process. Therefore, there is a need for a system that can provide solutions to problems that can currently be resolved.